Development of an EGFET pH sensor using tio2-pani composite thin films for soil characterization - Kamarozaman, Nur Syahirah; Mohd Masri, Aina Syakirah; Zulkifli, Zurita; Herman, Sukreen Hana (Universiti Teknologi MARA Cawangan Johor Kampus Pasir Gudang, 2025)
Regular pH soil testing is needed to ensure soil health and improve crop yield. This can be done through laboratory testing or utilizing a commercially available sensor. The soil lab test was unappealing due to inconvenient soil sampling procedures and a high cost. Commercial soil sensors, however, are an undesirable method due to their poor precision and reliability. Thus, this study aims to develop an effective and reliable soil sensor using a highly sensitive extended gate field effect transistor (EGFET) pH sensor based on TiO2-PANI composite thin film. The deposited sample was tested for pH application in the range of pH 2 to 12. The sample demonstrated a super-Nernstian behavior with 66.1 mV/pH and a linearity of 0.9931. Additional testing revealed that the sample exhibited good repeatability with a standard deviation of 0.49%, and a low drift rate of 4.96, 5.54 and 3.32 mV/h in pH 4, 7 and 10, respectively for 6 hours, indicating that the sample is stable in the long term. Besides, the laboratory test and direct characterization via soil EGFET measurements were compared. The results show that the fabricated TiO2-PANI composite thin film in this work is beneficial for soil testing